283 The impact of charlson's comorbidity index in overall survival for advanced epithelial ovarian cancer. (18th September 2019) - Nunes, R; Mantoan, H; Goncalves, B; Faloppa, C; Kumagai, L; Badiglian-Filho, L; de Brot, L; da Costa, A; Baiocchi, G
Abstract : Objectives: To evaluate the impact of Charlson's Comorbidity Index (CCI) in overall survival of advanced epithelial ovarian cancer. Methods: We retrospectively analyzed a series of 82 patients with advanced epithelial ovarian cancer (Stages IIIA-IV) from 2009 to 2015. Clinical and pathological variables were extracted from medical-records. Patients were categorized according to CCI in 3 groups: low (0–1), intermediate (2–3) and high (≥4). Results: The median age was 57 years and 62(78.5%) were high-grade serous tumors. Forty-five (54.9%) cases had primary cytoreductive surgery, 33(40.2%) interval cytoreduction and 4(4.9%) staging surgery. Five (6%) patients had stages IIIA-IIIB tumors, 64(78%) stage IIIC and 13(15.8%) stage IV. Sixty-one (75.3%) cases had no residual disease after cytoreduction and 10(12.3%) residual disease ≤1cm. The median Surgical Complexity Score (SCS) was 6 (0–15) and 11 cases (14.7%) had major complications (NCI grade ≥3), including 3(3.6%) deaths within 30 days after surgery. The CCI were low, intermediate and high in 38(46.9%), 36(44.4%) and 7(8.6%) cases, respectively. Notably, CCI was not related to major complications (p=0.3). The median OS and PFS were 70.5 and 20.2 months. The median OS for patients with low, intermediate and high CCIs were 91.8, 51.6 and 38.9 months, respectively (p=0.11). However, CCI impacted PFS, as median PFS for patients with low, intermediate and high CCIs were 32.1, 16.2 and 13.4 months, respectively (p=0.004). Moreover, major complications negatively impacted OS compared to minor complications (91.8 vs.22.1; p=0.002), but not PFS (20.2 vs.22.2; p=0.71). Conclusions: Our data suggest that higher CCI negatively impacted PFS in advanced ovarian cancer.